It's the Specification, Stupid! - Broy, Manfred; Ruess, Harald; Shankar, Natarajan (Communications of the ACM, 2025)
In this article the authors challenge the current state of the test-fix-test coding cycles for software development and propose formal verification. The consideration of specification in formal verification is discussed as well as timing of verification. Topics include big specifications and front-loading as well as the role of large language models in this process.